2002
DOI: 10.1128/iai.70.8.4369-4378.2002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acid Adaptation on the Fate of Listeria monocytogenes in THP-1 Human Macrophages Activated by Gamma Interferon

Abstract: In Listeria monocytogenes the acid tolerance response (ATR) takes place through a programmed molecular response which ensures cell survival under unfavorable conditions. Much evidence links ATR with virulence, but the molecular determinants involved in the reactivity to low pHs and the behavior of acid-exposed bacteria within host cells are still poorly understood. We have investigated the effect of acid adaptation on the fate of L. monocytogenes in human macrophages. Expression of genes encoding determinants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 63 publications
3
39
1
Order By: Relevance
“…Transcription of plcA, which is involved in vacuolar escape and cell-to-cell spread, is decreased by 12% after acid adaptation. In contrast, increased transcription of sodC (310%) and the combined gad genes (3000%) was observed after acid adaptation (47). It is interesting that while Hly and PlcA are both expressed in the phagosome and contribute to vacuolar escape, the pH ranges for their enzymatic activities are different (96,99).…”
Section: Listeria Monocytogenesmentioning
confidence: 89%
See 2 more Smart Citations
“…Transcription of plcA, which is involved in vacuolar escape and cell-to-cell spread, is decreased by 12% after acid adaptation. In contrast, increased transcription of sodC (310%) and the combined gad genes (3000%) was observed after acid adaptation (47). It is interesting that while Hly and PlcA are both expressed in the phagosome and contribute to vacuolar escape, the pH ranges for their enzymatic activities are different (96,99).…”
Section: Listeria Monocytogenesmentioning
confidence: 89%
“…Following activation of the macrophages, the rate of invasion of acid-adapted and nonadapted cells remained equal. However, the active macrophages became nonpermissive to growth of the nonadapted cells while acid-adapted cells demonstrated a greatly enhanced intracellular growth rate (47).…”
Section: Listeria Monocytogenesmentioning
confidence: 99%
See 1 more Smart Citation
“…While s B -dependent opuCA transcription under salt stress has been reported previously, the current study establishes reference values for transcript levels of s B -dependent genes in extracellular L. monocytogenes at 37 u C, which were needed to characterize relative s B activity in intracellular L. monocytogenes. As Milohanic et al (2003) showed that the s B -dependent opuCA also may be co-regulated by PrfA, we measured expression of a second s B -dependent gene, gadA, [lmo2434 (Conte et al, 2002); which is also designated gadD (Wemekamp-Kamphuis et al, 2004) and gadD3 (Cotter et al, 2005)]. s B activity (as determined by gadA and opuCA transcript levels) in intracellular L. monocytogenes arrested in either the host cell vacuole or the host cell cytosol was higher than in unstressed, exponentially growing bacteria and lower than in bacteria exposed to extracellular environmental stresses.…”
Section: Discussionmentioning
confidence: 99%
“…In what might appear to be contrary to the above processes of (producing=excreting) acid products, this study observed different levels of induction of decarboxylases such as the lysine decarboxylase (lmo2694) and glutamate decarboxylase (GAD) (lmo2434), which produce alkaline end products (Cotter et al, 2005) in AS and AA (Table 2). Induction of the latter (GAD) system is suggested to increase the pH of the immediate cell environment by a number of processes, including the export of g-aminobutyrate (Conte et al, 2002;Wemekamp-Kamphuis et al, 2004). The GAD system has been extensively reported as a key system in the adaptation of Listeria and other pathogens (Olier et al, 2004;Wemekamp-Kamphuis et al, 2004) to acid challenge in the human stomach (Blankenhorn et al, 1999).…”
Section: Energy and Metabolismmentioning
confidence: 99%